Analisa Perencanaan Regional - Tangerang Selatan - Jumino Jumino; Edi Mulyanto (Pekobis : Jurnal Pendidikan, Ekonomi, dan Bisnis, 2021)
This study intends to analyze sectoral economic development in South Tangerang City, as a study of Regional Economics. Talking about Regional Economics is certainly not talking about an individual activity, but analyzing areas that have diverse potential and how to make policies to accelerate economic growth in all regions evenly. the main objectives of the economy are: full employment economic growth and price stability. There are several things that can be better regulated in the regions, and are additional main objectives, namely: environmental sustainability, equitable regional development, determination of leading sectors in the region, creating better linkages between sectors in the region, so that it becomes more synergistic and sustainability and Fulfillment of regional needs. The purpose of this research is to be able to use it as a regional economic development and a stimulus for a wider and systematic movement of economic activity, in planning the potential of sectors: slow growing nationally, uncompetitive sectors and backward sectors, in order to grow and developing, to be implemented in South Tangerang, as a buffer zone for the economy of the capital city of Jakarta.